Business communication - .; Krizan, A. C. Buddy; Merrier, Patricia; Jones, Carol Larson (Cincinnati, Ohio : South-Western College, 1999)
This book is divided into six parts: The communication environment; Developing communications; Correspondence applications; Employment communication; Written report applications; and Oral and nonverbal communication.
Keywords: Business communication; Business communication